Pengaruh Interaktivitas dan Keahlian terhadap Niat Beli pada Fitur Shopee Live Melalui Kepercayaan pada Streamer sebagai Mediasi - Putri Nusadrina Murni; Ryna Parlyna; Fildzah Shabrina (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effect of streamer interactivity and expertise on consumer purchase intention within the Shopee Live feature, utilizing trust in the streamer as a mediating variable. Using a quantitative approach with a survey design, primary data were collected online from 210 respondents in DKI Jakarta selected through purposive sampling. Data analysis was conducted using the Structural Equation Modeling - Partial Least Squares (SEM-PLS) method with SmartPLS 4.0 software. The results demonstrate that both interactivity and streamer expertise have a positive and significant direct effect on purchase intention, as well as on the formation of consumer trust. Trust in the streamer is also proven to have a positive and significant effect on purchase intention and partially mediates the relationship between interactivity, streamer expertise, and purchase intention. This model explains 55.8% of the variance in trust and 54.5% in purchase intention, empirically supporting the Stimulus-Organism-Response (S-O-R) framework. For managerial implications, businesses are advised to train streamers in responsive two-way communication and comprehensive product knowledge to maintain credibility. Future research is recommended to expand the demographic scope and incorporate additional variables such as streamer attractiveness or broadcast quality.